Analysis of the Spectrum of ACE2 Variation Suggests a Possible Influence of Rare and Common Variants on Susceptibility to COVID-19 and Severity of Outcome - Shikov, Anton E.; Barbitoff, Yury A.; Glotov, Andrey S.; Danilova, Maria M.; Tonyan, Ziravard N.; Nasykhova, Yulia A.; Mikhailova, Anastasia A.; Bespalova, Olesya N.; Kalinin, Roman S.; Mirzorustamova, Azizahon M.; Kogan, Igor Yu; Baranov, Vladislav S.; et al. (Frontiers in Genetics, 2020)
Objectives: In March 2020 World Health Organization declared that an infectious respiratory disease caused by a new severe acute respiratory syndrome coronavirus 2 SARS-CoV-2 (COVID-19) became a pandemic. In our study, we have analyzed a large publicly available dataset, the Genome Aggregation Database (gnomAD), as well as a cohort of 37 Russian patients with COVID-19 to assess the influence of different classes of genetic variants in the ACE2 gene on the susceptibility to COVID-19 and the severity of disease outcome. Results: We demonstrate that the European populations slightly differ in alternative allele frequencies at the 2754 variant sites in ACE2 identified in the gnomAD database. We find that the Southern European population has a lower frequency of missense variants and slightly higher frequency of regulatory variants. However, we found no statistical support for the significance of these differences. We also show that the Russian population is similar to the other European populations when comparing the frequencies of the ACE2 variants. Evaluation of the effect of various classes of ACE2 variants on COVID-19 outcome in a cohort of Russian patients showed that common missense and regulatory variants do not explain the differences in the disease severity. At the same time, we find several rare ACE2 variants (including rs146598386, rs73195521, rs755766792, and others) that are likely to affect the outcome of COVID-19. Our results demonstrate that the spectrum of genetic variants in ACE2 may partially explain the differences in severity of the COVID-19 outcome.